Routine CD4 cell count monitoring seldom contributes to clinical decision‐making on antiretroviral therapy in virologically suppressed HIV‐infected patients. Issue 3 (18th September 2014) - Chow, EPF; Read, TRH; Chen, MY; Fehler, G; Bradshaw, CS; Fairley, CK
<x xml:space="preserve">Abstract</x> Objectives In Australia, CD4 cell count is monitored approximately every 6 months in HIV‐infected patients during antiretroviral therapy (ART). The aim of this study was to determine if routine CD4 monitoring contributed to decisions on changes to ART, and to estimate how reduced CD4 monitoring could contribute to cost savings in Australia. Methods We conducted a retrospective cohort analysis investigating all HIV‐infected patients who attended the Melbourne Sexual Health Centre (MSHC) in Australia from 1 April 2011 to 1 October 2013. We reviewed the electronic medical records of all patients who changed or stopped antiretroviral regimens during this time period to determine whether CD4 cell count could have contributed to this clinical decision. Results Among 1004 patients with HIV infection on ART, none [95% confidence interval (CI) 0–2.3%] of the 162 clinical decisions to change or stop treatment were influenced by CD4 cell counts. Reducing the current biannual CD4 monitoring strategy to annually could potentially save ∼AU 1.5 million (US 1.4 million) each year in Australia [i.e. ∼AU 74 700 (US 67 700) could be saved per 1000 HIV‐infected patients during ART]. Conclusions Routine CD4 monitoring in HIV‐infected patients during ART could be reduced from biannually to annually, as it rarely influences clinical decisions in patients' management. Not only could this avoid patients being unnecessarily anxious about normal fluctuations in their CD4 counts but it would also result in cost savings.